Enhanced Fertigation Control System towards Higher Water Saving Irrigation - Muhammad Khairie Idham Abd Rahman; Mohamad Shukri Zainal Abidin; Salinda Buyamin; Mohd Saiful Azimi Mahmud (Institute of Advanced Engineering and Science, 2018)
Water saving in agriculture is increasingly important due to critical issues of water and climatic crisis. The focus of agricultural researches nowadays is to minimize the water consumption and at the same time increasing the agricultural yield. This paper presents the three-types of automatic fertigation controller for irrigation system with different application tools. A weather station, soil moisture and timer based system were used to determine the volume of water supply needed by plants to calculate an accurate irrigation operation timing. The experiment was conducted by supplying water for capsicum annum test crop located in a greenhouse. The plant water demand parameter was calculated and compared for each application tools and the best application tool was chosen to be implemented in controlling the irrigation system.